Mesoporous carbon film via spin coating soft templating method for supercapacitor electrode - Sarif @ Mohd Ali, Mahanim; Zainal, Zulkarnain; Hussein, Mohd Zobir; Wahid, Mohd Haniff (2018)
Mesoporous carbon films were prepared by using spin coating self-assembly soft templating method onto titanium foils as substrates. A surfactant of triblock copolymer Pluoronic F127 (F127) which act as structure directing agent for the pore structure geometry tuning while preparing the mesoporous carbon film and carbon precursor of resorcinol (R) and formaldehyde (F) was used in the study. It was then carbonized to obtain the final product of F127/RF carbon film. The samples were characterized by electrochemical analysis. The carbonized F127/RF film show excellent electrochemical property for supercapacitor application and the specific capacitance 15.23 mFcm-1 at 5 mV s−1 scan rate was obtained using electrolyte of 1.0 M potassium chloride (KCl) neutral aqueous solution. These results suggest that the mesoporous F127/RF carbon film coated titanium foil is a promising candidate for high performance electrodes for electric double layer capacitors (EDLC).